Soil and fine roots ecological stoichiometry in different vegetation restoration stages in a karst area, southwest China. (15th December 2019) - Su, Liang; Du, Hu; Zeng, Fuping; Peng, Wanxia; Rizwan, Muhammad; Núñez-Delgado, Avelino; Zhou, Yaoyu; Song, Tongqing; Wang, Hua
Abstract: The cyclic process of carbon (C), nitrogen (N), and phosphorus (P) elements is an important factor affecting the function of the forest ecosystem. However, the relation between soil and root stoichiometric ratios, especially in karst areas with extremely fragile geology and intensive human disturbance has rarely been investigated. In the current study the concentrations of C, N, and P and their stoichiometric characteristics were investigated using sequential soil coring under different stages of vegetation restoration (primary forest, secondary forest, shrubland and grassland) and soil layer (0–10 cm, 10–20 cm, 20–30 cm) in fine root and soil samples. The results showed that total C concentration had no significant change in all four vegetation types and three soils layer in the fine root, whereas total N and P concentration reached the maximum value in secondary forest and the minimum in grassland. In addition, soil organic C (SOC) and total N increased continuously with natural succession and decreased with soil depth. Secondary forest showed the largest total P concentration in soil, with the smallest corresponding to grassland. Furthermore, both vegetation type and soil layer significantly affected soil C, N, and P stoichiometric ratios. There was a positive correlation among C, N and P in the fine roots, as well as in the soil. While fine root C:N and C:P ratios were negatively related to soil C:N and C:P, fine root N:P was significantly related to soil N:P. This study can provide a scientific basis for the restoration of fragile ecosystem vegetation and for comprehensive treatment of rocky desertification in karst. Highlights: Root and soil stoichiometry produced a great response with vegetation succession. In the karst area, plants fine root are limited by phosphorus in each restoration stages. Soil organic carbon and nitrogen are relatively stable at each restoration stages. Root nutrient use efficiency is associated with soil nitrogen utilization.